ANALISIS AMANAT DALAM PUISI “PANGGUNG SANDIWARA ” KARYA IKA MUSTIKA - Vivin Kusmiati; Nursiti Fatimah; Dida Firmansyah; Rosi Rosi (IKIP Siliwangi, 2019)
This research aims to find out the message contained in the poem